KARAKTERISTIK FILM TIPIS TiO2 DOPING NIOBIUM - Bilalodin Bilalodin; Mukhtar Effendi (Universitas Jenderal Soedirman, 2010)
Niobium (Nb) doped Titanium dioxide (TiO2) thin films have been successfully grown using spin coating method. Characterizations of thin films was carried out using EDAX (Energy Dispersion Analysis for X-Ray), XRD (X-Ray Diffaction) and SEM (Scanning Electron Microscope) to determine the microstructure of thin films. Determination microstructure, particularly of crystal structure was examined using ICDD data, whereas porosity calculation was done using the toolbox application on Matlab 6.1 software. EDAX, XRD and SEM characterization show that the thin films grown well at the Si substrates with the (002) field orientation is dominant and the thin film has the rutile structure. The TiO2 : Nb thin films product have granules round, uniform grain size and porosity value of about 41%.